Family Functioning and Moral Development of Students - Jerković, Ljiljana S.; Ilić, Mile Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
This paper presents the results of an empirical study into the relationship between family functioning and the level of moral development in senior students (adolescents), designed and conducted to take into consideration the more complete definition of the modern family, which gives preference to intra-family determinants over its external features, and relies on the results of previous relevant studies of the influence of the family on the formation of the child’s personality. A functional and healthy family is one that aspires to or successfully achieves its goal of raising and educating children and youth, responsible parenthood/guardianship, promotion and maintenance of the mental and physical health of all family members, and provision of support to their work, life, and social fulfillment.The aim of the study was to ascertain whether there is a statistically significant correlation between family functioning and the level of students’ moral development and overall school performance. It included 220 senior primary school students. The results show that about two-thirds of students see their families as optimally functional, and that the rest of the respondents believe that they live in families that do not reach the same functioning mark. Every third respondent perceives their family as functioning adequately, but quite a few students (7.27%) perceive their family as functioning moderately (according to the Beavers Systems Model, such families are considered dysfunctional). Students from optimally functional families had the highest average scores on moral development tests, while those from moderately functional families scored the lowest average number of points. The differences are statistically significant not only on these tests, but also for overall school performance as the control variable. A statistically significant correlation was found between the level of family functioning and student achievement on moral development tests. Such results allow us to conclude that family functioning (with all intragroup determinants that have positive educational effects) is one of the key factors in the moral formation of young people’s personalities and their academic performance. Therefore, itis extremely important to improve the social position of the family, continuously train/instruct parents on pedagogical issues, and continuously work in partnership with pedagogical and other institutions and organisations engaged in children’s upbringing and education.